Determination of limiting nutrient to Sweetpotato (Ipomoea batatas (L.) growth on Samoa Oxisol using a Nutrient Omission Technique - Siose, Taniela Kepa; Kader, Mohammed Abdul; Tulin, Anabella B. (Annals of Tropical Research, 2017)
This study was conducted to investigate the influence of various macro- and micronutrients on the growth and root yield of sweetpotato (variety IB/PH/03) grown in a Samoan Oxisol under semi-controlled screenhouse conditions. The following nutrient elements were considered: N, P, K, Mg, S, B, Cu, Fe, Mo, Mn, Ni, and Zn. The set-up involved pot nutrient omission trials wherein the twelve nutrient elements were combined to form an ALL treatment with subsequent 12 treatments made by excluding one nutrient consecutively from the ALL combinations. Treatments were arranged in a randomized complete block design with four replications for all treatments while six for the ALL treatment. Results showed that P was the most limiting factor to sweetpotato vegetative growth and root yield. Reduced storage root yield in relation to ALL were also observed when N, P, K, S, B, Fe, Mn, Mo and Ni were not supplied, although the difference was insignificant. Thus unless P deficiency is addressed, the deficiency effects of these nutrients on storage root yield remain insignificant.